2000
DOI: 10.1051/animres:2000140
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and coagulation properties of modicana and holstein cows' milk

Abstract: -The chemical composition and clotting properties of milk from 45 Modicana (Mo) and Holstein (Ho) cows were assessed over the winter (December and January) and spring periods (March-April). The cows came from 4 farms of the Ragusa region (Italy). Considerable differences in milk yield, milk composition and clotting properties were noted between breeds. During the winter and spring periods, Mo and Ho produced an average 15.4 and 35.8 kg . day -1 of milk, respectively. The Mo milk contained significantly more fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
2
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 13 publications
3
12
2
4
Order By: Relevance
“…These values are consistent with those summarised by Gaucheron (2005) in a review on cow milk minerals. Also, Ca content was close to findings of Chiofalo et al (2000) in a study on Modicana local cattle breed. The most variable milk mineral was Na (CV ¼39.75%), whereas the most stable were P (CV ¼11.44%) and K (CV ¼11.36%).…”
Section: Major Milk Mineralssupporting
confidence: 84%
“…These values are consistent with those summarised by Gaucheron (2005) in a review on cow milk minerals. Also, Ca content was close to findings of Chiofalo et al (2000) in a study on Modicana local cattle breed. The most variable milk mineral was Na (CV ¼39.75%), whereas the most stable were P (CV ¼11.44%) and K (CV ¼11.36%).…”
Section: Major Milk Mineralssupporting
confidence: 84%
“…Very few authors have studied the effect of breed on the properties of dairy products in interaction with the feeding system (Chiofalo et al, 2000;Ferlay et al, 2006). We showed that the No cows produced more yellow cheeses.…”
Section: Discussionmentioning
confidence: 85%
“…[8] twierdzą, że sposób żywienia ma wpływ na zawartość frakcji białkowych (kazeiny, białek serwatkowych) i składników mineralnych (wapnia, magnezu i cytrynianów), których ilość i proporcje mają istotny wpływ na proces krzepnięcia mleka. Uzyskany w badaniach własnych krótszy czas krzepnięcia mleka może być również związany z faktem, że w gospodarstwach stosujących tradycyjny system żywienia utrzymywano krowy ras lokalnych, a liczne badania [2,5,7,12] potwierdzają, że mleko od takich zwierząt charakteryzuje się korzystniejszymi parametrami do przetwórstwa, szczególnie do produkcji serów. Chiofalo i wsp.…”
Section: Wyniki I Dyskusjaunclassified
“…Chiofalo i wsp. [5], porównując parametry określające przydatność mleka dwóch ras krów do produkcji serów, tzn. modicana (lokalna) i holsztyńskiej (wysoko produkcyjna), wykazali, że mleko tej pierwszej charakteryzuje się korzystniejszymi wynikami, tzn.…”
Section: Wyniki I Dyskusjaunclassified
See 1 more Smart Citation